How do people with disabilities cope while waiting for disability insurance benefits? - Norma B. Coe; Stephan Lindner; Kendrew Wong; April Wu (IZA Journal of Labor Policy, 2014)
Disability Insurance waiting time varies from a few months to several years. We estimate the causal effect of longer waiting times on the use of five financial coping strategies. We find that SNAP benefits are the most responsive to longer waiting times. Moreover, while spousal employment is not responsive to longer wait times, spousal employment leads to longer waiting times, presumably because these applicants are more able to appeal. Together, these results suggest that coping strategies are used to both help applicants during the wait time and to extend the waiting time and increase their probability of success.
Keywords: H53; J08; I3; 330; Social security disability insurance; Waiting time; Disability; Instrumental variables; Supplemental Nutrition Assistance Program (SNAP); Added worker effect